SERVANT LEADERSHIP AND NURSE’S PRO-ENVIRONMENTAL BEHAVIOR: THE ROLE OF AUTONOMOUS AND EXTERNAL MOTIVATIONS - Bibi, Annam (Dinasti Publisher, 2020)
This study aims to investigate the relationships between servant leadership, pro-environmental behavior, and external and autonomous motivation among nurses, and whether external and autonomous motivations mediate the relationship between servant leadership and pro-environmental behavior. Based on a survey of 351 nurses, we found that servant leadership was significantly associated with pro-environmental behavior and that external and autonomous motivations indirectly affected the relationship between servant leadership and pro-environmental behavior. Moreover, servant leadership was found to interact with external motivation to predict pro-environmental behavior of nurses. Managers of nursing services should consider servant leadership and its positive influence on nurses’ outcomes in order to improve their performance and, subsequently, the healthcare system.